Production of proteinaceous antifungal substances from Lactobacillus plantarum ALAC‐4 isolated from Inner Mongolian traditional fermented dairy food. (20th June 2017) - Chen, Zhongjun; Li, Xiaoting; Gao, Hechen
Abstract : Lactic acid bacteria are of interest to the food industry due to their antimicrobial properties. In this study, five strains of Lactobacillus plantarum were isolated from traditional fermented dairy food in Inner Mongolia; the strains displayed antifungal characteristics . Lactobacillus plantarum ALAC‐4 was selected for further study due to its strong inhibitory effect on fungal development. The antifungal substances produced by L. plantarum ALAC‐4 were characterised based on treatments with heat, pH and enzymes. The antifungal metabolites were analysed using gel‐filtration chromatography and SDS‐PAGE. The results showed that the antifungal substances were heat stable and active against most of the tested fungi, and maximal activity was observed at pH values from 4.0 to 4.5. The antifungal activity was decreased by protease treatments, which indicated the proteinaceous nature of the antifungal substances. Enhanced antifungal activity occurred after 28 h of incubation in de Man, Rogosa, Sharpe (MRS) broth with a 4% inoculum level at 34 °C and initial pH of 7.0, which resulted in an increase from baseline data. The molecular mass of the antifungal substance determined by SDS‐PAGE was approximately 40.32 kDa. This study demonstrated that L. plantarum ALAC‐4 produces a peptide with a remarkable antifungal activity, which can be potentially used as a biopreservative in dairy products.